New Frontiers in Functional and Molecular Imaging of the Acutely Injured Lung: Pathophysiological Insights and Research Applications - Musch, Guido (Frontiers in Physiology, 2021)
This review focuses on the advances in the understanding of the pathophysiology of ventilator-induced and acute lung injury that have been afforded by technological development of imaging methods over the last decades. Examples of such advances include the establishment of regional lung mechanical strain as a determinant of ventilator-induced lung injury, the relationship between alveolar recruitment and overdistension, the regional versus diffuse nature of pulmonary involvement in ARDS, identification of the physiological determinants of the response to recruitment interventions and the pathophysiological significance of metabolic alterations in the acutely injured lung. Taken together, these advances portray multimodality imaging as the next frontier to both advance knowledge of the pathophysiology of these conditions and to tailor treatment to the individual patient’s condition.